The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s40069-012-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Shear Behavior and Performance of Deep Beams Made with Self-Compacting Concrete

Abstract: An experimental study was carried out to evaluate fresh properties of a moderately high-strength (high-flowing) selfcompacting concrete (SCC) and to investigate shear behavior and performance of deep beams made with SCC. Fresh and hardened properties of normal concrete (NC) and SCC were evaluated. The workability and compacting ability were observed based on casting time and number of surface cavities, respectively. Four-point loading tests on four deep beams (two made with SCC and two with NC) were then condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…The failure mode of deep beams was usually shear failure rather than flexure failure. It has been widely shown that the shear capacity of RC deep beams increased as the strength of the concrete and web reinforcement ratio increased [ 23 , 24 , 25 ]. FRC deep beams exhibit smaller crack widths and higher ultimate loads than those of RC deep beams [ 26 , 27 , 28 , 29 , 30 ] researched the flexural behavior of RC and FRC deep beams.…”
Section: Introductionmentioning
confidence: 99%
“…The failure mode of deep beams was usually shear failure rather than flexure failure. It has been widely shown that the shear capacity of RC deep beams increased as the strength of the concrete and web reinforcement ratio increased [ 23 , 24 , 25 ]. FRC deep beams exhibit smaller crack widths and higher ultimate loads than those of RC deep beams [ 26 , 27 , 28 , 29 , 30 ] researched the flexural behavior of RC and FRC deep beams.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that there was a 35 to 45% reduction in shear strength of simply supported SCC deep beams and higher mid-span deflection compared with their NC counterparts [6] owing to the lower amount and smaller size of coarse aggregate used in SCC mixtures. A number of studies on simply supported SCC deep beams [5,13] pointed out that the experimental shear capacity is much higher than that predicted by the shear provisions of the ACI 318-08. However, the prediction of the STM suggested by the ACI 318-08 was reasonably close to the experimental results of simply supported SCC deep beams [5] .…”
Section: Introductionmentioning
confidence: 92%
“…11(c)) (Mohammadhassani et al 2011). In Self compacting concrete (Choi et al 2012) and prestressed concrete deep beams (Tan et al 1999) failure mode is shear compression ( Fig. 11(e)).…”
Section: Size Effect In Rc Deep Beamsmentioning
confidence: 99%